Enculturation Pengaruh Lingkungan Sosial terhadap Pembentukan Perilaku Budaya Individu - Gea, Antonius Atosökhi (Bina Nusantara University, 2011)
In some research of culture and psychology, there has been found diversity cultural differences. Based on the fact, appeared questions like how it all started; what happens during the developing area that make humans from different culture has different attitude and behavior; what effects caused by environment like parents, peers, schools and social organizations for the differences. These questions are interesting to be found the answers, because it could give basic understanding about the cause of cultural attitude and behavior differences. This article is not purposed to answer all the questions, but it will try to find out how the enculturation process happens based on the existed research result. The discussion will be focused on the influence of parents, siblings, peers, and other organizations like daycare, education and religion system.